Emission of gas and atmospheric dispersion of SO2 during the December 2013 eruption at San Miguel volcano (El Salvador, Central America). Issue 14 (30th July 2015) - Granieri, Domenico; Salerno, Giuseppe; Liuzzo, Marco; La Spina, Alessandro; Giuffrida, Giovanni; Caltabiano, Tommaso; Giudice, Gaetano; Gutierrez, Eduardo; Montalvo, Francisco; Burton, Michael R.; Papale, Paolo
Abstract San Miguel volcano, El Salvador, erupted on 29 December 2013, after a 46 year period characterized by weak activity. Prior to the eruption a trend of increasing SO2 emission rate was observed, with all values measured after mid‐November greater than the average value of the previous year (~310 t d−1). During the eruption, SO2 emissions increased from the level of ~330 t d−1 to 2200 t d−1, dropping after the eruption to an average level of 680 t d−1. Wind measurements and SO2 emission rates during the preeruptive, syneruptive, and posteruptive stages were used to model SO2 dispersion around the volcano. Atmospheric SO2 concentration exceeded the dangerous threshold of 5 ppm in the crater region and in some sectors with medium elevation of the highly visited volcanic cone. Combining the SO2 emission rate with measured CO2/SO2, HCl/SO2, and HF/SO2 plume gas ratios, we estimate the CO2, HCl, and HF outputs for the first time on this volcano.